The effectiveness of the storyboard strategy in developing some literary appreciation skills among fourth grade students - Jaber, Jumana Abdul Hakim (Al-Adab Journal, 2015)
Thissearchaims to define the effectiveness of the storyboard strategyfor developing of some literary appreciation skills in poetic texts among grade four pupils in basic education in the Syrian Arab Republic, in order to achieve this goal, the researcher identify literary appreciation skills appropriate for students, and build a literary appreciation test. Using a quasi-experimental approach has been applied research tools on a sample of (70) pupils from primary stage schoolsin basic educationin the city of Homs, has been teaching poetic texts of the experimental group using storyboards, while the control group studied the traditional way followed by the teacher in the classroom. The results showed the presence of statisticallyindication differences between the scores of the application pre and post in the acquisition of pupils to literary appreciation skills in both experimental and control groups, Resultsrevealed the superiority of the experimental group students on the students of the control group test the literary appreciation, and in the light of previous results presented study some of the recommendations in the use of a strategy to expand storyboard in teaching the rest of the branches of the Arabic language